From Villoro to Nancy: The imposible community (Devenires, 2008)
From the perspectives, the latin-american Luis Villoro and the european Jean- Luc Nancy, in this article the author tries to make an aproximation to the necessity of clarity in the philosophical dialogue terms, not just because of the existance of several comunities but the different ways of comprehension of reality, the senses that give the world a particular meaning and the experiences that the humans are capable of from different latitudes of the world. The main point is to go forward in the comprehension of inter-cultural and interphilosofical of the idea of community.
Keywords: Villoro; Nancy; Community